2019
DOI: 10.5144/0256-4947.2019.403
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of human papillomavirus in Jeddah, Saudi Arabia

Abstract: BACKGROUND: Human papillomaviruses (HPVs) are small, non-enveloped, double-stranded DNA viruses that consist of more than 200 genotypes. Low-risk genotypes are associated with warts or benign lesions, whereas high-risk genotypes are usually associated with malignancies and cancers including cervical cancer. However, the real prevalence and incidence of HPV in Saudi Arabia may be understated due to a lack of comprehensive data reporting.OBJECTIVES: Determine the positivity rate of HPV in men and women in Jeddah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 30 publications
2
25
0
Order By: Relevance
“…Our data showed that 66% ( n = 16/24) of patients positive for HR HPV were younger than 40 years and 21% ( n = 5/24) were in their 5th decade, while 13% were older than 50 years. Age distribution of 31–50 was documented in a study in the western region of Saudi Arabia [30]. In a study carried out in Madinah, it was 46.7 ± 11.0 years [43].…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data showed that 66% ( n = 16/24) of patients positive for HR HPV were younger than 40 years and 21% ( n = 5/24) were in their 5th decade, while 13% were older than 50 years. Age distribution of 31–50 was documented in a study in the western region of Saudi Arabia [30]. In a study carried out in Madinah, it was 46.7 ± 11.0 years [43].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…The prevalence and genotype distribution of HR HPV infection detected in women with negative or abnormal cytology is not well known (according to “ HPV and Related Diseases Report ” in Saudi Arabia published by the “HPV Information Center” in December 2018). Some studies have been conducted about this subject from different regions in Saudi Arabia [29, 30]; however, none of them was from the Eastern area. Therefore, we aimed to highlight the prevalence and genotype distribution of HR HPV and correlate its association with cervical lesions detected on Pap tests in a conservative society in the Eastern Province of Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…In Saudi Arabia, the epidemiological picture of genital HPV infection is not well established because of the scarcity of population-based studies and the common belief that, as a sexually transmitted disease, HPV infection is not prevalent in conservative Saudi society [ 23 ]. The few available data showed HPV detection rates of less than 10% among healthy women [ 24 , 25 ], which is remarkably lower than the global figures. However, these rates increased to 32% in hospital-based samples [ 26 ] and to 43% in women with evocative symptomatology [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence and genotype of high-risk HPV infection detected in women with normal or abnormal cytology; ASCUS, LSIL, and HSIL) are so far unknown (according to “HPV and related diseases report” in Saudi Arabia published by the “HPV information center” on December 2018) [22, 23]. Our study aims to highlight the prevalence and genotype distribution of high-risk HPV infection and its association with cervical cancer and precancerous lesions in the Eastern-Province and other areas in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%